Is Information Asymmetry a Disruptive Factor in Food Consumer Behavior During the COVID Pandemic? - Socoliuc, Marian; Grosu, Veronica; Ciubotariu, Marius-Sorin; Brînzaru, Simona-Maria; Cosmulese, Cristina Gabriela (Frontiers in Nutrition, 2022)
Food quality and safety, on the one hand, increasing consumer awareness and changes in food policy due to the COVID-19 pandemic on the other hand, are today’s highly debated topics in the literature. Our research aims to understand the means of adjusting the food offer according to the request manifested by young and educated people and the impact of the information asymmetry on the consumers’ behaviour in the context of COVID-19. The objectives of the study focus on: O1 - exploring the nature of the informational asymmetry and the extent to which it usually affects the consumers' perception; O2 - identifying the prevalent socio-economic factors that influence the consumers' behaviour regarding their perception of the food quality products; O3 - quantifying the impact of the information asymmetry on consumers’ behaviour, both under conditions of economic stability and multiple crises (health and economic). In this study, a questionnaire survey that was applied among 529 young and educated people was used to design a cumulative analysis in order to allow a forecast based on a future trend of the food policies in relation to the changes in the consumers’ behaviour induced by the informational asymmetry and the COVID-19 effects, this being a method that allows for easy identification of changes in consumers’ behaviour in the food segment. The results of the survey led both to the identification of a quantification model of the information asymmetry that manifests itself within the relationship between the producer and the consumer and to the identification of a typology of informational asymmetry which manifests itself differently, depending on the features of the food products. The change in consumer behaviour under pandemic conditions has led producers to identify new strategies on how to transmit product information with effects on information asymmetry. The study can be useful for those entities that want to identify the changes in the typology of consumption according to certain criteria, in order to correlate their offer with the consumers' requirements, as well as for the national or regional institutional bodies with a role in developing food policies adapted to these requirements.